Wie Laien zu Leviten wurden: zum Ort der Korachbearbeitung innerhalb der Redaktionsgeschichte von Num 16-17 - Berner, Christoph (Biblische Notizen, 2012)
The study deals with the advanced and late stages in the literary development of Num 16-17. For a long time, these stages are dominated by the further literary growth of the narrative of the 250 lay people who propagate the ideal of a theocracy without priests (cf. 16:3, 35; 17:12*). This claim is refuted e.g. in 17:6-10, 15b and 17:16-24 where additional proof for the legitimacy of the Aaronic priesthood is provided. Only when Num 17 has almost reached its present literary form, the “Korachbearbeitung” (16:1a, 5a*, 6bβ, 7b, 8-11, 16a, 17a; 17, 5a*bα, 14b) shifts the focus on a conflict between priests and Levites. In a final step, Korach is depicted as the seducer of the entire community who shares the fate of Datan and Abiram (16:7a*, 16b, 17b, 18*, 19-22, 23-24 [LXX], 27a [LXX], 32b).